Between local culture, leisure activity, and nonreligion – the individual constructions of religion by adolescents in rural Austria - Koch, Anne (Religion, 2026)
The article presents a four-fold typology of adolescent constructions of religion in rural Austria. At first, it identifies the major types of ‘religion as part of local culture’ and ‘religion as leisure activity’ that dominate group discussions among adolescents in rural Austria. In addition, the article identifies two marginal types of ‘explicit nonreligion’ and ‘highly individualized religion’ that dominate the individual constructions of religion by some of those adolescents. These typological considerations are based upon empirical data from the TRANSMISSION research consortium on the constructions of religion by Austrian rural youth. Within the course of three years (2020–2023) the consortium undertook and analyzed 15 group discussions with adolescents from Alevi, Sunni, Catholic, Protestant, and Secular backgrounds. The comparative analyses are in the tradition of the Documentary Method. They lead to an intersectional analysis of the dynamics of adolescents within the religiously pluralized (but still largely hegemonic Catholic) Austrian context.